Resolving Accomodation Deficit at PT. Freeport Indonesia an Analysis Approach Using NPV Calculation - Pasaribu, Franky; Anggono, Achmad Herlanto (The Indonesian Journal of Business Administration, 2012)
PT Freeport Indonesia, which operates since 1972 succeeded in maintaining the sustainability of the company to date with ongoing exploration activities to increase proven mine reserve deposit.Discovery of the Grasberg open pit in 1988 made the PT Freeport Indonesia as one of the important players in the world of mining industry the proven copper is one of the largest in the world. PT Freeport is not going to stop at the Grasberg mine alone, therefore in 2004 Big Gossan underground mine was developed in 2008 and the underground mine Grasberg Block Cave. Several other mines are also being developed such as underground mine Deep Mine Level Zone (DMLZ) and Kucing Liar. Development of new mines and increasing production capacity requires a huge investment in terms of finance, technology, and labor. The rapid increase in employment was not followed by the addition of a decent accommodation facilities. PT Freeport Indonesia is currently facing substantial deficits accommodation.Deficit accommodation currently covered by the provision of temporary accommodation that are not habitable for the long term. PT Freeport Indonesia should immediately address the deficit that reached 2,282 units in 2011 and an estimated deficit of 2,193 units by the end 2012.There are three options that can be undertaken by PT Freeport Indonesia to overcome the accommodation deficit: 1)Delaying the expansion of the underground mine so there is no additional labor.2) Move some employees to the Jakarta office by office space leased at Jakarta or to buy and build their own offices.3) Increase the capacity of accommodation in the work area of PTFI, additional accommodation could be gained by building new units or by applying the concept of a limited mining town. Analysis method used is NPV, where the selection will be based on the smalles cost of the investment or the smallest cash outflow. This method is taken because accommodation is not the core business of the company but it is a cost center.Conclusion form NPV calculation, capacity expansion inferred by applying mining town is the best option for PTFI. Keywords: Accommodation deficit, mine expansion, NPV analysis.